Effects of different shelters on feeding, molting, survival, and growth of Scylla paramamosain - Zhou, Dongping; Liu, Lei; Huang, Xinlian; Fang, Wei; Fu, Yuanyuan; Li, Yuquan; Wang, Chunlin (Frontiers in Marine Science, 2023)
Providing shelters is considered an effective method to prevent self-harm and improve the survival rate of Scylla paramamosain. In this study, four shelter groups—the shelters of which included fine sand, arched tiles, PVC pipes, and trapezoidal net cages—and one group without shelters were established to investigate the effects of shelters on S. paramamosain by calculating their feeding rate, molting rate, survival rate, and growth index. The results showed that the feeding rates of the fine sand and PVC pipe groups were greater than 12% and that the feeding rates of the arched tile and trapezoidal net cage groups were greater than 9%, while the feeding rate of the group without shelters was only 6.7%. The food conversion rates of both the fine sand and PVC pipe groups exceeded 21%. In contrast, the food conversion rate of the non-shelter group was the lowest at 14%. The molting rates of the fine sand and PVC pipe groups were the highest, reaching 29% in the later stages of the experiment, while the molting rate of the non-shelter group was only 19%. There was no significant difference in survival rates among the groups during the first 20 days of the experiment. However, on the 60th day, the survival rate of the fine sand group was 92%, while the non-shelter group had a survival rate of 79%. The experimental results showed that the incidence of cheliped injuries in the fine sand group was 16%, while it was 25% in the non-shelter group. During the daytime, the occupancy rate of burrows by the four shelter groups was 60–70%, while during the night, the occupancy rate of each shelter decreased to 40–50%, and there was no significant difference in occupancy rates among the shelter groups during the night. The weight and full carapace width of S. paramamosain in the fine sand and PVC pipe groups were significantly higher than those in the other groups (P< 0.05), and the weight gain rate and specific growth rate of the fine sand and PVC pipe groups were significantly higher than those of the other groups (P< 0.05). Research has shown that fine sand and PVC pipes, as shelters for S. paramamosain, can effectively prevent cannibalism, increase feeding rates and survival rates, and promote growth and molting. This study provides scientific guidance for the proper selection of shelters in the farming process of S. paramamosain.